2021
DOI: 10.3390/atmos12091143
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Spring Air Temperature Forecast Skills of BCC_CSM1.1 (m) by Spatial Disaggregation and Bias Correction: Importance of Trend Correction

Abstract: In this study, an improved method named spatial disaggregation and detrended bias correction (SDDBC) based on spatial disaggregation and bias correction (SDBC) combined with trend correction was proposed. Using data from meteorological stations over China from 1991 to 2020 and the seasonal hindcast data from the Beijing Climate Center Climate System Model (BCC_CSM1.1 (m)), the performances of the model, SDBC, and SDDBC in spring temperature forecasts were evaluated. The results showed that the observed spring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Currently, the improvement of the model simulation ability is mainly focused on reducing uncertainty in climate change prediction by establishing some relationship between observations and simulations [67,68]. However, this method is vulnerable to the influence of the quality of observed data, physical processes and even the subjective consciousness of researchers [64].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the improvement of the model simulation ability is mainly focused on reducing uncertainty in climate change prediction by establishing some relationship between observations and simulations [67,68]. However, this method is vulnerable to the influence of the quality of observed data, physical processes and even the subjective consciousness of researchers [64].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the model data are interpolated to the station by inverse distance weighting (IDW). The control point number of neighbors of IDW is 4, and the weighting function is the inverse power of the distance [41]. Secondly, the interpolated data of the model are bias-corrected based on the station observation data using the quantile mapping approach, which focuses not only on the mean of the distribution but also on correcting the quantiles of the distribution [40][41][42][43].…”
Section: Bias Correction Methodsmentioning
confidence: 99%
“…The control point number of neighbors of IDW is 4, and the weighting function is the inverse power of the distance [41]. Secondly, the interpolated data of the model are bias-corrected based on the station observation data using the quantile mapping approach, which focuses not only on the mean of the distribution but also on correcting the quantiles of the distribution [40][41][42][43]. The cumulative probability distribution function (CDF) of the daily maximum air temperature is first estimated from the simulation data in the calibration period , and then the corresponding percentile values of the model projections are found.…”
Section: Bias Correction Methodsmentioning
confidence: 99%
“…In another operational climate modelling system, NMME, the warming trends in monthly mean temperature forecasts for both multi-model ensemble means and individual model forecasts were weaker than the trends in observations at all lead times (Krakauer, 2019). More recently, Duan et al (2021) evaluated the trends in spring temperature forecasts produced from the BCC-CSM1.1 (m) seasonal forecasting model operated by BCC. The significant warming trends in the observations were under-estimated by the model forecasts over 1991-2020 across most parts of China.…”
Section: Trend Mismatch Issuementioning
confidence: 99%
“…Jia et al (2014) demonstrated that the climate trend in the atmosphere enhanced seasonal forecast skill in the Northern Hemisphere, particularly across the Eurasian continent. Duan et al (2021) revealed that the skill of spring temperature forecasts over China was improved after trend bias was corrected. In contrast, precipitation skill was found to rarely benefit from the explicit representation of the observed trends in the climate model.…”
Section: Trend Mismatch Issuementioning
confidence: 99%